Analysis of the Phase Composition and Microstructure of Slag from a Semi-Steel Converter - Chenxiao, Li; Yongcong, Wei; Peng, Zhao; Kaixuan, Zhang; Qianqian, Gao; Zikang, Feng (Archives of Foundry Engineering, 2026)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:25135059-bb5b-4fbe-8621-c6dbe0fc3c4c-5" data-turn-id-container="request-WEB:25135059-bb5b-4fbe-8621-c6dbe0fc3c4c-5" data-testid="conversation-turn-12" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-8 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="ed3ab308-6bb8-4169-890a-b0c138b1b5ce" data-turn-start-message="true" data-message-model-slug="gpt-5-6-thinking"> To clarify the phase composition, microstructural characteristics, and phosphorus retention mechanisms of semi-steel converter slag, this study employed characterization techniques such as XRD, SEM-EDS, FTIR, and Raman spectroscopy to systematically compare the mineral composition, phosphorus retention patterns, and microstructure of semi-steel converter slag with those of single-slag converter slag. The results show that the main mineral phases in both types of slag are C2F, C2S, and the RO phase; in single-slag converter slag, phosphorus primarily exists as n-dicalcium silicate-tricalcium phosphate solid solutions, with a small amount tending to be fixed in the glass phase and other phosphates; in semi-steel converter slag, phosphorus is enriched in the form of nC2S-C3P solid solutions and C3P, with a small amount present in the glass phase and phosphorus-containing solid solutions; Both types of slag are composed of phosphates, silicates, and iron-aluminum coordination structures, with relatively low siloxane polymerization degrees, and P-O-P and P-O-Si are not major structural units. However, there are significant differences in the iron coordination environment: in semi-steel converter slag, iron primarily exists as FeO4 tetrahedra and FeO6 octahedra, whereas in single-slag converter slag, iron tends to form FeO4 tetrahedra; furthermore, the silicon and phosphorus group content and network polymerization degree in single-slag converter slag are significantly higher than those in semi-steel converter slag. This study provides a theoretical basis for the resource utilization of converter slag and the optimization of smelting process parameters.